2021
DOI: 10.1007/s00228-021-03089-x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin in people with dementia, long-term benefits, and harms: a systematic review

Abstract: Purpose People with dementia may have indications for aspirin prescription and clinicians are asked to balance the potential risks against benefits. This review examines the evidence for the risk and benefit of long-term aspirin use in people with dementia aged over 65 years, including randomised controlled trials and observational studies. Methods We searched three databases for research published between 2007 and 2020. Each eligible article was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…In line with this finding, among subjects without dementia, Waldstein and colleagues found that NSAIDs use was associated with slower decline on several cognitive domains [ 11 ]. However, another study using the Epidemiology of Hearing Loss Study of participants suggested that the use of aspirin was not associated with progression to cognitive deficits (MCI or dementia diagnosis) [ 20 ], which was consistent with other previous studies [ 14 , 21 26 ]. One potential explanation of these inconsistencies is that this association may be modified by the clinical stages.…”
Section: Discussionsupporting
confidence: 88%
“…In line with this finding, among subjects without dementia, Waldstein and colleagues found that NSAIDs use was associated with slower decline on several cognitive domains [ 11 ]. However, another study using the Epidemiology of Hearing Loss Study of participants suggested that the use of aspirin was not associated with progression to cognitive deficits (MCI or dementia diagnosis) [ 20 ], which was consistent with other previous studies [ 14 , 21 26 ]. One potential explanation of these inconsistencies is that this association may be modified by the clinical stages.…”
Section: Discussionsupporting
confidence: 88%
“… 35 The risk of major cardiovascular events like cerebrovascular accidents and myocardial infarctions is related to many factors that are also risk factors for dementia, including age and cardiovascular disease. 36 Antithrombotics such as aspirin are prescribed to people with dementia for reducing the risks of major cardiovascular events. 36 Our study reported that more than half of ADR-related hospitalizations were due to renally related ADRs.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Antithrombotics such as aspirin are prescribed to people with dementia for reducing the risks of major cardiovascular events. 36 Our study reported that more than half of ADR-related hospitalizations were due to renally related ADRs. Contrary to this, most studies have reported bleeding as the most common ADR-related diagnosis of hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Nos casos de CCV sem evidência de AVC prévio, a terapia deve ser individualizada 53 , principalmente em indivíduos com risco significativo de quedas. Nos últimos anos, não foram publicados estudos que comprovem os benefícios dos antiagregantes na evolução do CCV 54 ; • Estatinas: As estatinas são de interesse na prevenção secundária da doença cerebrovascular devido aos seus efeitos hipolipemiantes e pleiotrópicos na função vascular, que se combinam para inibir a aterosclerose. Há boas evidências de que as estatinas administradas tardiamente a pessoas em risco de doença vascular não previnem o declínio cognitivo ou a demência 55 .…”
Section: Tratamento Do Comprometimento Cognitivo Vascularunclassified
“…In cases of VCI without evidence of previous stroke, therapy should be individualized 53 , especially in individuals with significant risk of falls. In recent years, no studies have been published providing support for the benefits of antiaggregants in the evolution of VCI 54 ; Statins: Statins are of interest in the secondary prevention of cerebrovascular disease due to both their lipid-lowering and pleiotropic effects on vascular function, combining to inhibit atherosclerosis. There is good evidence that statins given late in life to people at risk for vascular disease do not prevent cognitive decline or dementia 55 .…”
Section: Treatment Of Vascular Cognitive Impairmentmentioning
confidence: 99%